Inteligencia emocional y aprendizaje colaborativo en los estudiantes del Colegio Parroquial Nuestra Señora de Loreto, Iquitos 2023 - Yumbato Nashnate, Lili Graciela (2024)
This is due to the fact that teachers do not implement appropriate strategies for group formation, as the interactions among students show a lack of emotional intelligence when working collaboratively. The main objective of the research was to determine the relationship between emotional intelligence and collaborative learning in students of the Colegio Parroquial Nuestra Señora de Loreto, located in Iquitos, during the year 2023. The methodology followed a basic research approach with a non-experimental design, transactional type, and relational level. A sample of 247 primary-level students, of both sexes, was selected. According to the descriptive results, the predominant category associated with emotional intelligence and collaborative learning among the students was at the intermediate level (37%), followed by the low (24%) and high (20%) levels. The inferential analysis concluded that there is a significant association between the variables studied, as evidenced by a p-value lower than the significance level of α=0.05. Furthermore, the relationship is direct and of high magnitude, as confirmed by a Kendall's Tau-B coefficient of 0.703.